نظم المعلومات الإدارية وتاءثير ها على ادارة الموارد البشرية والاداء الوظيفي في جحاز تنفيزمشروعات الاسكان والمرافق في ليبيا - Otman Belkasm Omar Algwizi
This study aimed to know the direct impact of management information systems on human resources management and functionality in implementation of housing projects and facilities device in Libya, also aimed to find out the indirect impact of management information systems on functionality through its impact on human resources management as a factor mediator. To achieve the objectives of the study a default model was developed and it expressed the relationship between the variables of the study, as the management information systems were considered an independent variable affects the human resources management as a mediator variable, and the functionality as a dependent variable .The researcher designed a questionnaire included 77 items, 304 questionnaires have been distributed to collect data from the study sample, a model study and its hypotheses have been tested using a combination of statistical methods, and that via the Statistical Package program for Social Sciences (SPSS), and the (Amos EMI) program ; for the application of linear equation modeling (SEM) . The study found that there is a direct impact of management information systems on human resources management and functionality. And there is an indirect effect of management information systems on functionality through its impact on human resources management.